Quand l’intime défie l’ordre colonial - Les couples de Malgaches et d'Européennes en Imerina (Hautes Terres centrales de Madagascar) de 1896 à 1960. - Violaine Tisseau (Genre & Histoire)
In 1896, Madagascar became a French colony. Mixed couples and their offspring as well as situations of interbreeding were perceived as a potential source of disorder. In this article, we are interested in unions between Malagasy men and European women. These couples were rare and mainly united Malagasy men with « métisses » women, in a regular marriage. Despite their rarity, the colonial authorities were initially tempted to forbid them, before making the marriage of Malagasy men with European women a condition for obtaining French citizenship. What lay behind this wavering was the fear of losing the colonizer’s prestige and a too great proximity between colonizers and colonized. Indeed, such unions show the existence of intimate and lasting relationships between Malagasy and Europeans. The intimate became a threat by questioning the coherence of the colonial order.